Comparison Analysis of Transmission Performance for COMI and CIMO Type Asynchronous Magnetic Couplers with Double-layer Solid Rotor - Yang Chaojun; Ji Chenglong; Zhang Xiuwen; Zhang Youjin; Yuan Airen; Zhang Xiaofeng (Jixie chuandong)
In order to study the transmission performance of the COMI and CIMO type coupler with the same structure parameters,the equivalent magnetic circuit method is used to analyze and derive the torque formula of the coupler,and the final torque expression is acquired by combining the torque formula and three dimensional correction coefficient. Also,the efficiency formula of magnetic coupler is derived. Then,the finite element simulations is used to analyze the transmission performance of the two kinds of couplers when they are under the same input speeds and slips ratio. The results indicate that COMI type coupler has the same transmission efficiency with the CIMO type coupler,but can get bigger torque when they have the same geometrical parameters,which means COMI type coupler has better transmission performance.